1992
DOI: 10.1002/aic.690380609
|View full text |Cite
|
Sign up to set email alerts
|

Uranium adsorption characteristics of a circulating fluidized‐bed adsorber

Abstract: A new type of fluidized bed, called a circulating fluidized-bed adsorber ( CFBA 1, was developed for processing a large quantity of water with high efficiency. Its fluid mechanical characteristics are reported, as well as recovery of uranium from natural seawater using a small CFBA. Using hydrous titanium oxide, granulated with polyacrylonitrile (PAN-HTO), as an adsorbent, CFBA ran stably for six days, the period required for the adsorbent to collect a practical amount of uranium. To predict the uranium adsorp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

1995
1995
2011
2011

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…To reach a continuous adsorption separation operation, a liquid−solid circulating fluidized bed (LSCFB) is a good choice. Studies on the hydrodynamics in the LSCFB can be found in recent literature. Ito et al used the LSCFB adsorber to extract uranium from seawater. Lan et al introduced a concept of LSCFB ion exchanger system for continuous recovery of biochemical products and studied the effect of operating conditions on the hydrodynamics and developed the successful application for the continuous recovery of bovine serum albumin (BSA).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To reach a continuous adsorption separation operation, a liquid−solid circulating fluidized bed (LSCFB) is a good choice. Studies on the hydrodynamics in the LSCFB can be found in recent literature. Ito et al used the LSCFB adsorber to extract uranium from seawater. Lan et al introduced a concept of LSCFB ion exchanger system for continuous recovery of biochemical products and studied the effect of operating conditions on the hydrodynamics and developed the successful application for the continuous recovery of bovine serum albumin (BSA).…”
Section: Introductionmentioning
confidence: 99%
“…Studies on the hydrodynamics in the LSCFB can be found in recent literature. [15][16][17] Ito et al 18 used the LSCFB adsorber to extract uranium from seawater. Lan et al [19][20][21] Industrial & Engineering Chemistry Research ARTICLE LSCFB ion exchanger system for continuous recovery of biochemical products and studied the effect of operating conditions on the hydrodynamics and developed the successful application for the continuous recovery of bovine serum albumin (BSA).…”
Section: Introductionmentioning
confidence: 99%
“…They unfortunately do not give the liquid axial dispersion coefficient used in the model. Ito et al [16] present a dispersive model for the adsorption of uranium in a circulating fluidized bed that they divide in slices. The number of slices, going from 1 to 30 depending on the simulations, does not affect the results significantly.…”
Section: Introductionmentioning
confidence: 99%